Pelatihan Pemanfaatan AI Berbasis Chatgpt untuk Meningkatkan Efektivitas dan Kemandirian Belajar Siswa di Kelas VIII SMP Negeri 27 Batam: Pengabdian - El Roy Manalu; Ida, Rame Irma; Laoli, Men Friu; Sopha, Deka Waro; Simbolon , Helen Kristina; Sembiring, Niska Maresa Br; Rina; Renny Victoria Sinaga; Yoseo Alpindo Prima; Paulina Nainggolan; Lukeria Gurning; Ester Yenisa Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A Community Service (PkM) activity entitled Utilization of ChatGPT-Based AI to Improve Student Learning Effectiveness was held at SMP Negeri 27 Batam. This activity focused on training students to use ChatGPT-based Artificial Intelligence technology productively. The main objective was to equip students with the digital and ethical competencies needed to utilize this intelligent tool to support their independent learning process. In the implementation of this PkM there were several stages: first, field observations conducted by the PkM committee. Second, the implementation of activities where in-depth socialization regarding the functions and limitations of AI, followed by a hands-on practice session using ChatGPT for its application in subjects. Third, Evaluation of activities where each participant will fill out a satisfaction questionnaire and also on reflection during the training. The results of this Community Service activity were participants' ability to think critically, increased interest in independent learning and mastery of digital developments. Therefore, through this training, it becomes the initial foundation and the right step in integrating artificial intelligence responsibly and ethically in the learning process to prepare students to face the challenges of the digital era.